SOSIALISASI PEMBERDAYAAN DAN PERAN PENTINGNYA DIGITALISASI GUNA MENINGKATKAN PRODUKTIVITAS UMKM - Firman; Novita Sari; Muhammad Sadril; Muhammad Aini; Muhammad Adz-Dzikri Suryanata; Imam Syuhada Lukman Hasibuan; Fandi Ahmad Yusuf; Edison Arianto; Dhea Narullita Sabrina; Christian Glorianus Sani; Yanuarius Risky Waga Ruga (Universitas Kadiri, 2025)
This activity is an UMKM empowerment program and the importance of digitalisation to increase the productivity of UMKM in Balikpapan city. This activity is a form of concern for economic development from the UMKM sector. The socialisation was conducted in Manggar Baru urban village, Balikpapan city. From this socialisation, it can be seen that the knowledge of the community of UMKM business actors is still lacking in understanding the use of technology to brand the products produced. With the socialisation programme, it is very helpful for the community to improve their business products including introducing them to consumers. Therefore, the socialisation on the importance of digitalisation for UMKM in Balikpapan City has succeeded in increasing the interest and understanding of business actors on the use of digital technology. The digitalisation of UMKM gives a positive impact to increase productivity and improve people's welfare. Utilisation of digital technology in the form of social media provides efficiency in terms of time, energy, and cost, increased market reach, and improved service quality.